Experimental and modelling studies on continuous synthesis and refining of biodiesel in a dedicated bench scale unit using centrifugal contactor separator technology. Issue 6 (19th August 2015) - Abduh, Muhammad Yusuf; Martínez, Alberto Fernández; Kloekhorst, Arjan; Manurung, Robert; Heeres, Hero J.
Abstract : Continuous synthesis and refining of biodiesel (FAME) using a laboratory scale bench scale unit was explored. The unit consists of three major parts: (i) a continuous centrifugal contactor separator (CCCS) to perform the reaction between sunflower oil and methanol; (ii) a washing unit for the crude FAME with water/acetic acid consisting of a mixer and a liquid–liquid separator; and (iii) a FAME drying unit with air. The continuous setup was successfully used for a 4 h runtime without any operational issues. The CCCS was operated at an oil flow rate of 32 mL/min, rotational speed of 35 Hz, 60°C, a catalyst concentration of 1.2% w/w and a methanol flow rate of 10 mL/min. The flow rate of water (containing 1% w/w acetic acid) for the biodiesel washing unit was 10 mL/min (20°C); the air flow rate (5% humidity) was set at 12 L/min. After 4 h runtime, approximately 7 kg of refined FAME was produced from a cumulative sunflower oil feed of 7.07 kg. The ester content of the refined FAME was 98% w/w (GC). Other relevant product properties were also determined and most were shown to meet the ASTM specifications. The refining section was modelled and optimised using ASPEN software. Practical applications: Synthesis and refining of sunflower biodiesel was successfully performed in a dedicated bench scale unit using centrifugal contactor separator technology. Besides for large scale biodiesel production, this technology has particularly potential to be applied in small mobile biodiesel units due to the compact size, robustness, flexibility in operation and high volumetric productivity of the CCCS devices. Schematic representation of the continuous bench scale unit. Abstract : Schematic representation of the continuous bench scale unit.